A Review of Practices Around Determination of Death by Neurologic Criteria by an Organ Procurement Organization in the WAMI Region. Issue 5 (October 2022) - Lele, Abhijit Vijay; Wahlster, Sarah; Bost, Ian; Adorno, Dominic; Wells, Candy; O'Connor, Kevin; Greer, David; Souter, Michael J.
Abstract : Background and Objective: To examine the verification of a referring hospital's practice of determining death by neurologic criteria (DNC) by an organ procurement organization (OPO) pursuant to the Center for Medicaid and Medicare Services rule §486.344(b). Methods: In this retrospective cohort study, we examined prevalence and factors associated with deviations from acceptable DNC standards, the performance of additional ancillary testing requested by the OPO, resolution of concerns about deviations between referring hospitals and the OPO, and interactions between referring hospitals and the OPO. Results: The OPO reviewed DNC processes for 645 adult potential organ donors from 64 referral hospitals. Concerns about practice deviations from acceptable standards were identified by the OPO's medical director (also a practicing neurointensivist) on call in 19% (n = 120) and were related to clinical prerequisites (27.2%, n = 49), clinical examination (23.9%, n = 67), and apnea testing (25.3%, n = 97). The top 3 concerns were apnea test results not meeting PCO2 targets (6.7%, n = 43), errors in documentation of the clinical examination (5.3%, n = 34), and potential confounding effects of CNS depressants (2.5%, n = 16). Compared with the "no medical director concerns" group which includes all patients, where the coordinator felt that DNC determination met all the conditions on the checklist, medical director concerns were less likely to occur in hospitals with a dedicated neurocritical care unit (odds ratio [OR] 0.33, 95% CI 0.17–0.66, p < 0.001), prevalent across hospitals independent of whether their policies conformed to updated DNC guidelines (OR 0.92, 95% CI 0.57–1.45, p = 0.720). The OPO requested additional ancillary testing (6%, n = 41) when clinical prerequisites were not met (OR 12.7, 95% CI 4.29–33.5), p < 0.001). Resolution of concerns and organ donation was achieved in 99.4% (n = 641). Four patients were rejected as brain-dead donors because of the presence of cerebral blood flow on the nuclear medicine perfusion test. Referring hospitals requested support from the OPO regarding the determination of DNC (10%, n = 64) and declaring physicians were reported to lack knowledge about the institutional DNC policy (4%, n = 23). Discussion: Ongoing review of institutional DNC standards and adherence to those standards is an urgent unmet need. Both referring hospitals and OPOs jointly carry responsibility for preventing errors in DNC leading up to organ recovery.